2016
DOI: 10.1177/1533034616670273
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of a Hybrid RapidArc Radiotherapy Technique for Locally Advanced Lung Cancer

Abstract: Objective: Radiation treatment planning for locally advanced lung cancer can be technically challenging, as delivery of !60 Gy to large volumes with concurrent chemotherapy is often associated with significant risk of normal tissue toxicity. We clinically implemented a novel hybrid RapidArc technique in patients with lung cancer and compared these plans with 3-dimensional conformal radiotherapy and RapidArc-only plans. Materials/Methods: Hybrid RapidArc was used to treat 11 patients with locally advanced lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Studies have shown an increased risk of radiation pneumonitis with a lung V5 > 60%. Silva et al compared hybrid VMAT, VMAT-only, and 3DCRT plans in patients with locally advanced lung cancer [ 9 ] and reported significant reductions in the dose to normal organs, including the lungs, using hybrid VMAT compared with the other plans. After a median follow-up time of 17 months, there was no symptomatic radiation pneumonitis in patients with a median V5 value of 57–58%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown an increased risk of radiation pneumonitis with a lung V5 > 60%. Silva et al compared hybrid VMAT, VMAT-only, and 3DCRT plans in patients with locally advanced lung cancer [ 9 ] and reported significant reductions in the dose to normal organs, including the lungs, using hybrid VMAT compared with the other plans. After a median follow-up time of 17 months, there was no symptomatic radiation pneumonitis in patients with a median V5 value of 57–58%.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid Rapid Arc plans were created with the combination of static (60%) and Rapid Arc (40%) beams and showed advantages for reducing the OARs dose. 33 We tried different fraction combinations for the hybrid plans in this study. We conclude that 45 Gy/18 fxs for TH and 25 Gy/10 fxs for TD is the best combination.…”
Section: Discussionmentioning
confidence: 99%
“…presented the clinical application of the hybrid Rapid Arc in patients with locally advanced lung cancer. Hybrid Rapid Arc plans were created with the combination of static (60%) and Rapid Arc (40%) beams and showed advantages for reducing the OARs dose 33 . We tried different fraction combinations for the hybrid plans in this study.…”
Section: Discussionmentioning
confidence: 99%